Aluminium–Polymer ABS product - Mohd Ichwan, Nasution; Shamsul Baharin, Jamaludin; Che Mohd Ruzaidi, Ghazali; Khairel Rafezi, Ahmad (Universiti Malaysia Perlis, 2010)
Organized by School of Materials Engineering & Sustainable Engineering Research Cluster, 1st - 2nd December 2009 at Putra Brasmana Hotel, Kuala Perlis, Perlis.